The THE EFFECTIVENESS OF LEARNING METHODS IN KNOWING THE CHARACTERISTICS OF CHANGES IN RESULTS STUDENT LEARNING: EFEKTIVITAS METODE PEMBELAJARAN DALAM MENGETAHUI KARAKTERISTIK PERUBAHAN HASIL BELAJAR PADA MAHASISWA - Aulia Kharisma Putri; Kurnia, M.E; Pramesti, W.S; Kunaepi, A (Fakultas Psikologi Universitas Borobudur, 2024)
This research aims to explore and evaluate the characteristics of changes in student learning outcomes through various learning methods applied. Learning methods play an important role in determining the effectiveness of learning and student learning outcomes. This research uses literature study and data analysis from various related data sources as well as collecting primary data by distributing questionnaires which are distributed to students. The research instrument is in the form of questions about learning outcomes after applying several methods and which is the most effective and has a very positive impact. The research results show that choosing the right learning method can increase students' understanding, motivation and skills. Based on research, the discussion method shows the greatest increase in learning outcomes compared to other methods. The implication of this research is the importance of paying attention to the changing characteristics of student learning outcomes in designing and implementing appropriate learning methods. It is hoped that this research can make a positive contribution to the development of learning strategies that are more effective and relevant for education in the future.